HOW DO NEGATIVE DESTINATION IMAGE ELEMENTS AFFECT DOMESTIC TOURISM? - Nikola Todorović (Zbornik Radova: Geografski institut "Jovan Cvijić", 2023)
Destination image perceptions have a strong impact on the visit intention of tourists. While positive representations of a destination affect this intention favorably, negative representations decrease it. During the first year of the pandemic, intensified tourist flows toward dominantly nature-based destinations influenced the increase of prices, crowdedness, and pressures on nature within them. These developments were covered by numerous media reports and were heavily present on social media, which is a strong channel for modifying image perceptions. This study aims to establish the strength of the presence of these negative image elements in the consciousness of tourists and the strength of the impact of these elements on the intention to spend the summer holiday in Serbia, as well as on the desire to spend the summer holiday at the seaside. During June and July of 2021, a survey was conducted among 234 participants. The collected data was analyzed through structural equation modeling (SEM). It was established that all three negative elements are moderately present in the image perceptions of domestic destinations, whereby overpricing was determined to be slightly more present than the excessive amount of visitors and nature endangerment. Despite this, the studied elements do not pose a negative impact on the tourists' intention to spend the summer holiday in the country. A strong positive effect of the perceived expensiveness of destinations (ED) on the desire to go to the seaside (DGS) was established.